(untitled) (Research, Society and Development, 2022)
The purpose of this study was to assess the distance between the mandibular canal and the base of the mandible in the mental foramen region, in order to determine sexual dimorphism in the Brazilian population. The assessment of this distance is also important to prevent injuries to the inferior alveolar neurovascular bundle and to avoid clinical complications during surgical procedures. Using the simplified Kalabalik and Aytuğarn method for studies in Forensic Dentistry or Anatomy, this study assessed 100 cone-beam computed tomography images of male and female patients. The distance between the inferior border of the mandibular canal and the base of the mandible in the mental foramen region was evaluated bilaterally. No significant statistical differences were found between the right and left sides of the mandible. However, statistically significant difference between the genders was found (p=0.038). The lower distance (D2) measure can be applied to determine sexual dimorphism in the Brazilian population. Further studies presenting larger samples are needed to confirm these initial findings.